Serbian press and Eastern Ortodoxy in Serbia in the 1980s - Dragišić, Petar (Poligrafi, 2025)
The paper examines Serbian press coverage of the resurgence of Eastern Ortho-doxy in Serbia during the 1980s. It is based on an analysis of the most influential daily, weekly, and monthly newspapers and magazines printed in Serbia between 1980 and 1990. The research aims to reconstruct perceptions of the revival of re-ligiosity in Serbia during this period and to identify its root causes. The research showed a close causal connection between the change in public perception of religion, that is, the revival of religiosity in Serbia, and the changed political en-vironment in former Yugoslavia in the 1980s. The research suggests that the esca-lation of tensions in Kosovo triggered the ethnic mobilization of Serbian society and consequently strengthened the influence of the Serbian Orthodox Church in Serbia in the late 1980s
Keywords: 1980-1990; 1980s; Eastern Ortodoxy; Jugoslavija; religiosity; religioznost; Serbia; Srbija; vzodno pravoslavje; Yugoslavia